Vermicompost Amended With Rock Phosphate as a Climate Smart Technology for Production of Organic Swiss Chard (Beta vulgaris subsp. vulgaris) - Ajibade, Sinazo; Mupambwa, Hupenyu Allan; Manyevere, Alen; Mnkeni, Pearson Nyari Stephano (Frontiers in Sustainable Food Systems, 2022)
Vermicomposting is being promoted as climate-smart agriculture (CSA) technology for developing organic nutrient sources that can be adopted by smallholder farmers. The amendment of soils with cost-effective and available inorganic fertilizers like rock phosphate (RP) and phosphorus-solubilizing microorganisms should also be promoted. Our study investigated the seedling and maturity growth of Swiss chard. The crop maturity study investigated the effect of amending an Oxisol soil with three phosphorus (P) sources applied at three different rates (0, 25, and 50 mg P kg−1 soil), cow and pig manures, and P-solubilizing bacteria resulting in the following treatments: control (soil), soil + RP alone, soil + RP-enriched cow manure vermicompost (VC) with phosphorus-solubilizing bacteria (PSB), and soil + RP-enriched pig manure vermicompost (VP) with PSB. The study investigated the growth performance and accumulation of copper (Cu), zinc (Zn), chromium (Cr), and lead (Pb) in the edible parts of Swiss chard (Beta vulgaris subsp. valgaris var. Cicla). The seedlings were grown using pine bark compost and the three P sources (VC, VP, and RP) at five different application rates (0, 25, 50, 75, and 100%). The results revealed that the use of 50 mg P kg−1 as VP gave the highest fresh weight of 39.78 g, leaf area of 240.41 cm2, and a total P in tissues of 326.91 mg kg−1 at 8 weeks after transplanting. The 50 mg P kg−1 application as VC resulted in a higher Zn content of 8.50 mg kg−1, which was above the permissible level. These results suggest that the best treatment mixture for establishing fully matured Swiss chard was the 50 mg P kg−1 as VP. Therefore, pig manure vermicompost that has been inoculated with phosphorus-solubilizing microorganisms is a promising CSA technology that can improve organic vegetable production by smallholder farmers.